Igreja, poder e imprensa : o ideário anticomunista no seminário sergipano A Cruzada(1937-1970) - Santos, Amanda Marques dos (2019)
This research investigates the anticommunist ideology of the Sergipe clergy from the newspaper A Cruzada, analyzing, for this, the matters of a political-ideological-religious nature. In this way, a comparative study is carried out between the Vargas Dictatorship (1937-1945) and the Civil-Military Dictatorship (1964-1985) through journalistic discourses produced by representatives of the conservative clergy and/or Christian intellectuals who collaborated in the production of this weekly, which marked the history of the state of Sergipe from 1918 to 1970. It is defended, therefore, the existence of a heterogeneity in conservative thinking about anti-communism presented in the newspaper A Cruzada. The journal is seen as a "network of sociabilities" that articulates the ideological debates and games of affinity of these intellectuals. It is considered that the anticommunist ideology was the discursive and ideological key for the deflagration of these two coups d'etat, that counted on distinct forms of military action of the armed forces, and can be seen as an opposition to ideology and the communist objectives. The discourse analysis was an important research methodology, which aligns itself to a perspective that understands it as a way of understanding the text from the subjects' symbolic and social fields. In this way, the newspaper A Cruzada was chosen because it is seen as a tool of propagation of the religious and ideological discourse of anticommunist bias, that was in force in the periods corresponding to Estado Novo and the Civil-Military Dictatorship. progressive on this theme, influenced by the social formation of the intellectuals involved in its production.